ROOTING OF DATE PALM (PHOENIX DACTYLIFERA L.) OFFSHOOTS BY ISOPROTHIOLANE (IPT) - Abdullatif. A. Alkhateeb; Suliman. A. Alkhateeb; T. Ohmura; R. Okawara; H. Ali-dinar (European Scientific Journal, ESJ, 2015)
The experiment was conducted at Alhassa Oasis (25° 22′ N' latitude; 49°34′ E longitude) and altitude is 179 m a.s.l , Kingdom of Saudi Arabia. Treatments included the following Isoprothiolane (IPT) concentrations incorporated at the bottom of offshoot hole: control (without IPT), 25g, 50g, 75g, 100g, 200g and 500g / offshoot hole. The offshoots weight ranged between 25 – 30 kg. The IPT concentrations of 75 and 100 g/ offshoot hole seemed to be quite optimal for improving rooting of date palm offshoots. The best rooting percentage, length of root, root fresh and dry weights were obtained under 75 and 100 g/ offshoot whole IPT concentrations. Offshoots under the control and the lowest and highest IPT treatments reflected poor rooting ability. The chlorophyll content data although looked relatively similar between treatments, a slight edge of 75 and 100 g/ offshoot hole was noticeable. This relative edge might have played a significant role in the photosynthetic ability of offshoots. The efficiency of rooting of offshoots under both concentrations might have resulted from their edged photosynthetic ability.